2009
DOI: 10.1111/j.1600-0579.2008.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Competencies in implant therapy for the dental graduate. Appropriate educational methods

Abstract: Modern dental education should have in on one hand the necessary education and training to make modern dentists capable of implementing population and individual preventive strategies, and on the other make them competent to satisfy current public demands to most patients. Amongst the restorative procedures most demanded by patients implant therapy has reached a clear pre‐dominance. Although specialists have traditionally rendered this therapeutic procedure, in simple cases there is seldom need for extensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 10 publications
(15 reference statements)
1
38
0
Order By: Relevance
“…Other professions have adopted similar approaches (Mezey, Mitty, Burger, & McCallion, 2008;Rousseau, Saucier, & Cote, 2007;Sanz & Saphira, 2009), in the development of training and education programs, particularly in the health sciences professions. Educational models used by these disciplines also include defined competencies that are achieved through a combination of knowledge building, experiential, and reflective learning.…”
Section: Discussionmentioning
confidence: 97%
“…Other professions have adopted similar approaches (Mezey, Mitty, Burger, & McCallion, 2008;Rousseau, Saucier, & Cote, 2007;Sanz & Saphira, 2009), in the development of training and education programs, particularly in the health sciences professions. Educational models used by these disciplines also include defined competencies that are achieved through a combination of knowledge building, experiential, and reflective learning.…”
Section: Discussionmentioning
confidence: 97%
“…Sanz and Shapira described the competencies to be achieved by a graduate dentist, related to information‐gathering, diagnosis, treatment planning, treatment and prevention and evaluation of treatment. In addition, it was postulated that dentists should be competent at designing and delivering effective implant‐supported restorations and have knowledge and limited clinical experience in surgical procedures at the basic (straightforward) level, based on the SAC classification .…”
Section: A Undergraduate Educationmentioning
confidence: 99%
“…These programmes have on average 72 ECTS credits, ranging 12 from 180. Respondents reported on average 9.5 students (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in the final year of study. Three of 11 respondents (27%) acknowledged that implant dentistry is a recognised specialty in their country, and 82% of the respondents (9/11) reported that the postgraduate programme has an official university recognition.…”
Section: Independent Implant Dentistry Programmesmentioning
confidence: 99%
“…It should include the fundamental principles of implant therapy, enabling graduates to integrate implant treatment into an overall concept of comprehensive care, to identify indications and contraindications and to inform patients about the treatment options (7). The educational approach used should be in line with modern insights about curriculum development, for example, competence-based education, student-centred, evidence-based, interdisciplinary, case-based and/or problembased learning (5). Postgraduate competences were identified in four domains: (i) clinical, (ii) management and leadership, (iii) communication and (iv) professionalism and ethics, at different levels of clinical practice (straightforward, advanced and complex) according to the need of general practitioners to specialists (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation